Effects of Consumption of Soft Drinks on the Muscular Morphology of Animals Submitted to Concurrent Training - Aleixo, Paulo Henrique [UNESP]; Santos, Lucas da Silva; Tamura Ozaki, Guilherme Akio; Garcia, Thiago Alves; Carvalho Zanuto, Everton Alex [UNESP]; Trindade Camargo, Regina Celi; Silva Camargo Filho, Jose Carlos; Castoldi, Robson Chacon [UNESP] (Soc Chilena Anatomia, 2019)
The consumption of industrialized foods and beverages contributes to the increase in body weight and manifestation of diverse illnesses. Among these industrialized products, soft drinks can be mentioned, which when consumed in large quantities can contribute to weight gain and the emergence of chronic non-communicable diseases such as hypertension, diabetes, and obesity. In terms of performance, several training protocols have been used, among which concurrent training is presented as a tool that can aid in the control of body weight and muscle development. Thus, the identification of dietary factors, as well as the use of appropriate training methods, can be essential factors in the increase in physical performance. To study the effects of concurrent training on the skeletal muscles of animals submitted to soft drink consumption. In the present study, 32 male rats were used, of the Wistar breed, in the post-weaning biological phase (30 days). The animals performed a concurrent training protocol. Forty-eight hours after the final training session, the animals were submitted to a surgical procedure to remove samples of gastrocnemius muscle. After preparation of the histological slides, the muscle fibers of the different groups of animals were measured. The median values for the minimum diameter of muscle fibers presented the following values: Control (C): 35.78, Control Soft Drinks (CSD): 36.93, Training (T): 39.12, and Training Soft Drinks (TSD): 37.82. The CSD and TSD groups demonstrated the greatest increase in body mass in relation to the C and T groups. In addition, the groups that performed the concurrent training presented a higher mean of the smallest fiber diameter. It was concluded that the ingestion of soft drinks had a negative effect on the muscular hypertrophy of animals submitted to a concurrent training protocol.
Keywords: Soft drink; Concurrent training; Skeletal muscle